Immobilization of Glucose Oxidase on Poly(vinyl alcohol): The Effect of Immobilization Temperature on Apparent Enzyme Activity - Wong, Fui Ling; Abdul-Aziz, Azila (2004)
Amperometric enzymatic glucose biosensors based on glucose oxidase (GOD) are the most widely used devices for continuous regulation of diabetics’ blood glucose levels. An effective glucose biosensor must contain an immobilized enzyme layer which is stable and is active for a sufficiently long time. For GOD immobilized on poly(vinyl alcohol) through chemical cross-linking, temperature plays an important role on the effectiveness of the cross-linking process. The higher the temperature, the faster the cross-linking process. In an attempt to minimize the possible denaturation of enzyme due to the exposure to the cross-linking temperature, the possibility of immobilizing GOD onto PVA at a lower temperature was investigated. For a hydrogel, membrane water content is generally a good indicator of the cross-linking density of a particular membrane. Thus, the performances of PVA-GOD membranes immobilized at either 4°C or 25°C but having similar water content were studied. However, no significant differences in the enzyme activity of both types of membranes were observed.